Dimensi-Dimensi Dalam Membangun Transparansi Pengelolaan Dana Desa: - - Rofiah, Nurul Khofifatur; Suryawati, Dina; Rohman, Hermanto (Universitas Dr. Soetomo Surabaya, 2023)
Transparency in Village Fund management is a critical issue today. By providing information that is true, full, adequate, and simple to grasp, transparency makes sure that the public has access to information about village funding and fosters confidence between the community and the administration. This research aims to develop dimensions to improve transparency in managing Village Funds. The rise of acts of corruption committed by village government officials in Indonesia has affected the level of public trust in the government. one of the efforts so that the level of public trust in the government does not decrease is throughTransparency in the management of Village Funds. The goal of this study is to create elements that will improve the administration of village funds in terms of transparency.Descriptive qualitative research is used in this study. Observation, interviews, and documentation were the data gathering techniques used in this study. The results of this study indicate that the dimensions that can build transparency in the management of village funds are: 1) regulatory guarantees that support transparency, 2) Transparency of the Village Financial Management Process through Deliberations and Public Communication 3) Accessibility and Media that Ensure Completeness and Clarity of Information and Budget Documents